2000
DOI: 10.1053/euhj.2000.2476
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the implantable cardioverter defibrillator secondary prevention trials

Abstract: on behalf of the investigators of the AVID, CASH and CIDS studies Aims Three randomized trials of implantable cardioverter defibrillator (ICD) therapy vs medical treatment for the prevention of death in survivors of ventricular fibrillation or sustained ventricular tachycardia have been reported with what might appear to be different results. The present analysis was performed to obtain the most precise estimate of the efficacy of the ICD, compared to amiodarone, for prolonging survival in patients with malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
303
1
22

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 970 publications
(332 citation statements)
references
References 11 publications
(6 reference statements)
6
303
1
22
Order By: Relevance
“…Several randomized clinical trials [1][2][3][4] provided evidence of increased survival in patients with resuscitated VT/VF who received an ICD compared with those who were treated with amiodarone. However, only the AVID study demonstrated a statistically significant mortality benefit of the ICD over amiodarone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several randomized clinical trials [1][2][3][4] provided evidence of increased survival in patients with resuscitated VT/VF who received an ICD compared with those who were treated with amiodarone. However, only the AVID study demonstrated a statistically significant mortality benefit of the ICD over amiodarone.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with an ejection fraction Ͼ35% in subgroup analysis appear to derive little or no benefit from the ICD over amiodarone in these trials. [1][2][3][4] In CIDS, younger patients with better NYHA functional class also appear to derive less benefit (over the time frame studied) from the ICD. 6 At the conclusion of CIDS, the steering committee made no formal recommendations regarding ongoing management of the patients assigned to amiodarone.…”
mentioning
confidence: 99%
“…For example, patients with advanced NYHA Class symptoms are associated with higher risk of death related to progressive heart failure, which potentially reduces the impact of ICD therapy. As noted previously, in a meta‐analysis of the secondary prevention RCTs, patients with LVEF ≥35% had significantly less benefit compared with those whose LVEF was severely reduced 36. Two such groups of patients who require special consideration are the elderly and those with chronic kidney disease.…”
Section: Special Patient Populationsmentioning
confidence: 78%
“…The first found significant reductions in deaths from all causes (HR 0.72; 95%CI 0.60‐0.87) and arrhythmia (HR 0.50; 95%CI 0.36‐0.67) with the ICD vs amiodarone 36, 37. There was no significant difference in nonarrhythmic death (HR 0.93; 95%CI 0.73‐1.17).…”
Section: Randomized Controlled Trials Of Icds and Guidelinesmentioning
confidence: 97%
“…Similarly, implantable‐cardioverter defibrillator implantation in the Utstein subgroup remained stable over time. Although revascularization is recommended for OHCA patients with ST‐segment–elevation myocardial infarction and predischarge implantable‐cardioverter defibrillator implantation is recommended in clinically appropriate patients, the present data set does not permit the adjudication of the appropriateness of these procedures 31, 32, 33…”
Section: Discussionmentioning
confidence: 89%